2020
DOI: 10.1186/s12883-020-01908-9
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, placebo-controlled, double-blind, pilot trial to investigate safety and efficacy of Cerebrolysin in patients with aneurysmal subarachnoid hemorrhage

Abstract: Asbtract Background There are limited neuroprotective treatment options for patients with aneurysmal subarachnoid hemorrhage (SAH). Cerebrolysin, a brain-specific proposed pleiotropic neuroprotective agent, has been suggested to improve global functional outcomes in ischemic stroke. We investigated the efficacy, safety and feasibility of administering Cerebrolysin for SAH patients. Methods This was a prospective, randomized, double-blind, placebo-controlled, single-center, parallel-group pilot study. Fifty … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…In the aneurysmal subarachnoid hemorrhage clinical retrospectively study, CBL injection during the acute period of SAH appeared to reduce the mortality rate, especially in poor-grade patients 44 , while a recent randomized, placebocontrolled, double-blind, pilot trial demonstrated that daily CBL (30 mL/day) is safe, well-tolerated, and feasible for SAH patients, but it does not improve the six-month global functional performance of patients 45 . In the present study, we found that CBL can improve early brain injury by alleviating brain edema and neuron necroptosis after SAH.…”
Section: Discussionmentioning
confidence: 97%
“…In the aneurysmal subarachnoid hemorrhage clinical retrospectively study, CBL injection during the acute period of SAH appeared to reduce the mortality rate, especially in poor-grade patients 44 , while a recent randomized, placebocontrolled, double-blind, pilot trial demonstrated that daily CBL (30 mL/day) is safe, well-tolerated, and feasible for SAH patients, but it does not improve the six-month global functional performance of patients 45 . In the present study, we found that CBL can improve early brain injury by alleviating brain edema and neuron necroptosis after SAH.…”
Section: Discussionmentioning
confidence: 97%
“…An observational retrospective clinical study also confirmed that CBL may improve the level of consciousness in stroke patients in a minimally conscious state 44 . A recent randomized, placebo-controlled, double-blind trial demonstrated that daily CBL (30 mL/day) is safe, well-tolerated, and feasible for subarachnoid hemorrhage patients, but it does not improve the six-month global functional performance of patients 45 . In the present study, we found that CBL can improve brain injury by alleviating brain edema, neuroinflammation, and neuronal apoptosis after TBI in animals and decrease neuroinflammation in TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical research on Cerebrolysin ® in the late subacute to chronic phases is still ongoing, with only 1 published retrospective study on the reduction of spasticity, and 1 in patients with minimally conscious state after stroke [ 16 , 17 ]. Additionally, sufficient safety data in several neurological conditions, such as subarachnoid hemorrhage, traumatic brain injury, and mild cognitive impairment and dementia, have been published [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%